2011
DOI: 10.1364/ol.36.003654
|View full text |Cite
|
Sign up to set email alerts
|

Optical-fiber pulse rate multiplier for ultralow phase-noise signal generation

Abstract: In this letter we report on an all optical-fibre approach to the synthesis of ultra-low noise microwave signals by photodetection of femtosecond laser pulses. We use a cascade of Mach-Zehnder fibre interferometers to realize stable and efficient repetition rate multiplication. This technique increases the signal level of the photodetected microwave signal by close to 18 dB, that in turn, allows us to demonstrate a residual phase noise level of -118 dBc/Hz at 1 Hz and -160 dBc/Hz at 10 MHz from 12 GHz signal. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(78 citation statements)
references
References 21 publications
0
72
0
2
Order By: Relevance
“…We expect to reach the 10 −16 level of accuracy in the near future with commercially available ground stations modified to apply the TWCP technique. Optically generated microwaves [25,26] …”
Section: Figmentioning
confidence: 99%
“…We expect to reach the 10 −16 level of accuracy in the near future with commercially available ground stations modified to apply the TWCP technique. Optically generated microwaves [25,26] …”
Section: Figmentioning
confidence: 99%
“…It should be possible to improve both by utilizing a higher repetition rate optical source. Modest reprate enhancement (up to few GHz) can be accomplished using compact mode-locked lasers [27], [28], or by employing an optical pulse interleaver [29]. Moving beyond a few GHz, one can utilize optoelectronic combs [30], [31], which provide additional flexibility in choice of center frequency, bandwidth, and repetition rate.…”
Section: Discussionmentioning
confidence: 99%
“…We have realized proof-of-principle experiments of such a scheme [37] and are now progressing toward implementing it in an operational system. We further demonstrated several advanced techniques [38][39][40] to reduce the imperfection of the frequency division and photo-detection processes. We have shown that it is now becoming possible to generate microwave signals with phase noise as low or lower than any other technology for a large range of Fourier frequencies.…”
Section: Optical Frequency Combsmentioning
confidence: 99%